Correlation Study of the Cone Penetration Test in the Field with a Laboratory Test on Soft Soil in Banjarmasin - Firdaus, Muhammad; Ruspiansyah (Jurnal Multidisiplin Madani, 2023)
The very soft soil commonly found in South Kalimantan, especially in Banjarmasin, with conditions of tidal swampy land, poses a challenge when it comes to the development of areas intended for medium-scale building construction. The demands of the population and the increasing need for housing necessitate the addition of residential levels, both by the government and private entities. This will undoubtedly open up new areas, and housing development will become a top priority in order to realize this. This research process is conducted in the field and in the laboratory, using soil material tested with the cone penetration test (CPT) method and data processing to identify the type and characteristics of the soil, ensuring they remain unchanged during the analysis of field data. Original samples are also taken for the purpose of analyzing the selection of foundation reinforcement types. Very soft clay soil is identified from the location of Gunung Meranti in Banjarmasin. This data is used for the analysis of bearing capacity, settlement analysis, characteristics, and identification, which will be correlated with the results of previous testing conducted in the laboratory using the Unconfined Compression Test (UDS) method in nearby locations. The results of field investigation data in the form of manometer readings are expected to assist the author as indicators in measuring and analyzing the type and characteristics of the soil, as well as the bearing capacity of the subgrade soil in the laboratory, based on the results of the CPT